(3OQGSI ebGQfIs - (3hSje fbhdG(B, (3CHh SYOs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2010)
1 ) (3fTCI OjhGf GdeMGSHI h JWhQ egGeg (B2) (3fWGb QbGHI OjhGf GdeMGSHI GdGOGQjI GdeSHbI (B: (3GdJcjja GdbGfhfj ddQbGHI GdeSHbI h GdfJGFL GdeJQJHI Ydi eNGdaI GMcGegG , GdLgGJ GdNGVYI dQbGHI GdOjhGf GdeSHbI h GdeYGedGJ GdNGVYI ddQbGHI GdeSHbI Cj GdeYGedGJ GdeJYdbI HGdhGQOGJ , GdeJYdbI HGdfabGJ , GdfJYdbI HGdeUGdMGJ h GdeYGedGJ GdeSJKfGI ef GdQbGHI (B3) (3GUhd eeGQSI GdQbGHI GdGOGQjI GdeSHbI (B: (3GdGLQGAGJ GdeegOI GdbQGQ , WQb GdeQGLYI HGdbQGQGJ GdUGOQI aj fWGb GdQbGHI GdeSHbI (B4) (3GdeYhbGJ h GdUYhHGJ GdJj JhGLg GdYed GdQbGHj (B( (3GdQbGHI GdeSHbI hGdeDNQI (B) (3GdPj jeGQSg GdOjhGf (B: (3GdeYhbGJ GdfJYdbI HGdSdWGJ GdNGVYI ddQbGHI , GdeYhbGJ GdeJYdbI HOjhGf GdeMGSHI (B5) (3GbJQGM GdZGA GdQbGHI GdGOGQjI GdeSHbI (B: (3eVehf eTQhY GdbGfhf h GdedGMVGJ Ydjg , JYRjR QbGHI GdOjhGf GdeSHbI (B6) (3GdQbGHI Ydi GdGOGA (B: (3JYQja GdQbGHI Ydi GdGOGA YfGUQgG h GgOGagG , GdQbGHI Ydi GdCOGA aj GdJTQjY GddHfGfj (B7) (3GdfJGFL GdeGdjI ddQbGHI GdeSjbI h GdbQGQGJ GdUGOQI HeYQVgG (B: (3GdQbGHI Ydi GYJOGd GdGSYGQ , CfhGY GdbQGQGJ GdJj JUOQ aj fWGb GdQbGHI GdeSHbI (B8) (3GdQbGHI GdeSHbI Ydi GdUabGJ GdYehejI (B: (3GdefGbUI GdYehejI , GSJOQGL GdYQhV , GdGJaGb HGdJQGVj , GdUabGJ ZH GdWdH h GdUabGJ HehLH HjGf Ch aGJhQI (B.s
Keywords: (3GdGOGQI GdeGdjIs; (3GdQbGHIs; (3GdeMGSHIs; (3GdeMGSHI GdGOGQjIs